Revitalization of Pogar Reservoir Tourism Through Reforestation: Its Impact on Community Awareness in Climate Control - M. Ubaidillah Ridwanulloh; Anisa Silviana; Cici Alfianti; Muh Fajar Syahrizal Ramadhan; Firdan Zanuar; Hasfizanatun Nisa'; Rif'an Munabila Taufik; Renita Donasari; Andika Eko Prasetiyo (Smart Society, 2023)
The function of reservoirs is crucial for storing water, especially during the rainy season. The ongoing issue at Pogar Reservoir is the barren condition of the area and the limited knowledge among the community regarding the reservoir's role in climate control. Based on these issues, efforts are needed to raise community awareness of the importance of reservoirs through revitalization activities at Pogar Reservoir. The community service method used is the Asset-Based Community Development (ABCD) approach. This service was carried out by a team in coordination with the local government. Additionally, socialization was conducted to help the community understand the proper management of the reservoir. The revitalization program was then implemented in the areas around the reservoir by planting Petai trees and others. The results of this service were appreciated by the local government and the community, with tree planting in the reservoir area, restoring the reservoir's function as a better-maintained green area, and turning it into a potential village tourism destination that supports local economic growth and small and medium-sized enterprises (SMEs). This revitalization also created job opportunities for the local community, and the previously barren reservoir area has become greener and better maintained.